IN 1945-1960, MUSLIM RELIGIOUS EDUCATIONAL INSTITUTIONS LIMITED THE TRAINING OF RELIGIOUS PERSONNEL (American Journal of Research in Humanities and Social Sciences, 2024)
This article describes the official permission to establish the Central Asia and Kazakhstan Muslim Administration, to open mosques, as well as the permission to train religious institutions and their subsequent restrictions during the Soviet rule.